Addressing Challenges in Endometriosis Pain Communication Between Patients and Doctors: The Role of Language - Bullo, Stella; Weckesser, Annalise (Frontiers in Global Women's Health, 2021)
Introduction: In the context of the complex medical, social, and economic factors that contribute to endometriosis diagnosis delay and its consequent impact on quality of life, this report focuses on patient-practitioner pain communication and examines the role of language in doctor-patient communication. Our study explored what patients and doctors consider challenging and effective in endometriosis pain communication. It further examined what commonly used metaphors by patients could be suggestive, or not, of endometriosis to doctors. Method: A United Kingdom-based qualitative (open-ended question) survey with women with endometriosis (n131) and semi-structured telephone interviews with general practitioners (GPs) (n11). Survey and interview data were analyzed thematically. Results: Both women and GPs reported the Numeric Rating Scale (NRS) to be insufficient as a standalone tool for communicating endometriosis related pain. Both also found descriptions of the quality, location, and impact on daily life of pain to more effective means of communicating pain symptoms. When presented with common metaphorical expressions surveyed women used to describe their pain, not all GPs recognized such metaphors as indicative of possible endometriosis. Further, some GPs reported some of the expressions to be indicative of other pathologies. Conclusion: Findings reveal the importance of language in pain communication and the need for additional tools to help women and doctors find the most effective way to communicate the experience and elicit appropriate investigative care. They also show the need for further investigation into how metaphor can be effectively used to improve patient-practitioner communication of endometriosis related pain.